Heat knife power supply technology for unfolding satellite solar panel based on super capacitor

By using supercapacitor-based hot knife power supply technology in satellite solar wind panels, high-performance supercapacitor modules and hot knife components are built using MXene/COF composite materials, the complex structure and operation of traditional solar wings during the deployment and recycling process are solved. Difficulties and other problems have achieved more efficient and reliable solar windsurfing operation and extended the life of the satellite.

CN119429190AActive Publication Date: 2025-02-14NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411253275.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-02-14
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

Traditional satellite solar wings have complex structure, difficult operation, and easy damage during the expansion and recycling process, which affects their stability and service life.

Method used

Using supercapacitor-based hot knife power technology, including supercapacitor modules, hot knife components and control circuits, MXene/COF composite materials are prepared through hydrothermal assisted synthesis method to build high-performance supercapacitor modules and hot knife components.

Benefits of technology

Improves the deployment and recycling efficiency of solar wind panels, simplifies the structure, reduces the risk of failure, improves the reliability and efficiency of operations, extends the life of the satellite, and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119429190A_ABST
    Figure CN119429190A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of spaceflight, and discloses a heat knife power supply technology for unfolding a satellite solar panel based on a super-capacitor, and the technology comprises a super-capacitor module which is used for storing electric energy; the heat knife assembly is made of a high-resistance material, is instantly heated by electrifying and is used for cutting a fixing device of the solar panel; the control circuit comprises a charging module, a discharging control module and a temperature monitoring module; the super capacitor module comprises an MXene and a COF composite electrode, and the composite electrode is prepared by the following steps: step 1, etching T < iVA > < l > C powder to obtain T < iVCT < x > MXene; step 2, mixing and dissolving tetraaminophenylenediamine and triformyl triphenylamine, and heating for reaction to obtain COF. In order to realize effective combination of COF particles and MXene, the research adopts a hydrothermal assisted synthesis method. According to the method, COF particles can grow on the surface of MXene in situ by utilizing a chemical reaction under a hydrothermal condition, so that a novel MXene / COF (MCF) composite material is formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of aerospace technology, and in particular to a hot knife power supply technology for deploying satellite solar panels based on supercapacitors. Background Art

[0002] With the rapid development of aerospace technology, more and more satellites are successfully launched into space. As an important part of the power subsystem, satellite solar panels play a vital role in satellites. Their function is not only to provide a stable power supply for satellites, but also directly affects the overall operation and life of satellites. In order to improve the energy collection efficiency of satellites and extend their service life, designing an efficient, stable and reliable solar panel deployment and recovery mechanism has become a research focus.

[0003] In the existing technology, traditional satellite solar panels are usually compressed by pyrotechnics such as cutters, and the solar panels are unlocked by the detonation of pyrotechnics after entering orbit. This type of device has the advantages of strong carrying capacity, short action time and high synchronization, but it also has insurmountable disadvantages, such as poor safety, non-reusability, difficult to verify reliability, large impact loads and possible pollution. As a new type of energy storage device, supercapacitors have great application value in military satellite systems due to their ultra-high reliability, stability, tolerance to harsh environments, and support for ultra-large current rapid charging and discharging. Therefore, non-pyrotechnic connection and separation devices based on supercapacitors have become a hot topic of research.

[0004] The main problem with the existing technology is that the traditional pyrotechnic devices have poor safety, cannot be reused, and are difficult to verify reliability during the deployment and recovery of satellite solar panels. These shortcomings not only increase the operational risks of satellites, but may also shorten the service life of solar panels in the space environment, thereby affecting the overall performance of the satellite. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a hot knife power supply technology for deploying satellite solar panels based on supercapacitors, which solves the problems that traditional solar panels may encounter during the deployment and recovery process, such as complex structure, difficult operation, and easy damage, which affects their stability and service life.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A hot knife power supply technology for deploying satellite solar panels based on supercapacitors, comprising:

[0007] Supercapacitor modules for storing electrical energy;

[0008] The hot knife assembly is made of high-resistance material and generates heat instantly when powered on, and is used to cut the fixtures of the solar panels;

[0009] A control circuit, including a charging module, a discharging control module and a temperature monitoring module;

[0010] The supercapacitor module includes a MXene and COF composite electrode, and the composite electrode is prepared by the following steps:

[0011] Step 1: Etch TiVAlC powder to obtain TiVCT x MXene;

[0012] Step 2: Mix tetraaminophenylenediamine and trialdehyde triphenylamine, dissolve them and heat them to react to obtain COF;

[0013] Step 3: React MXene with tetraaminophenylenediamine and trialdehyde triphenylamine solution under hydrothermal conditions to form a MXene / COF composite material.

[0014] Preferably, in step 3, the specific capacitance calculation formula of the electrode material is:

[0015]

[0016] Where I is the discharge current, Δt is the discharge time, m is the mass of the electrode material, and ΔV is the voltage change.

[0017] Preferably, the TiVCT x The preparation steps of MXene specifically include:

[0018] Add 1.0 g of lithium fluoride to 20.0 mL of 9 M hydrochloric acid solution and stir for 20 minutes;

[0019] Slowly add 1.0 g TiVAlC powder, transfer to an oil bath, and react at 45 °C for 48 hours;

[0020] After the reaction, the mixture was centrifuged at 3500 rpm for 5 minutes using an ultra-high speed centrifuge, the supernatant was removed, and the mixture was washed repeatedly until the pH was neutral to obtain TiVCT. x MXene aqueous solution;

[0021] The obtained TiVCT x Freeze drying of MXene aqueous solution to obtain TiVCT x MXene powder.

[0022] Preferably, the preparation steps of the COF specifically include:

[0023] Dissolve 0.015 mM tetraaminophenylenediamine and 0.02 mM trialdehyde triphenylamine in 10 mL of a mixed solvent of o-dichlorobenzene and n-butanol in a volume ratio of 1:1;

[0024] The reaction was heated at 120°C for 48 hours;

[0025] After the reaction was completed, the COF solid was separated by suction filtration and washed with anhydrous ethanol;

[0026] The COF powder was obtained by freeze drying to remove the solvent and water in the COF.

[0027] Preferably, the preparation steps of the MXene / COF composite material specifically include:

[0028] 2 mg MXene and 7 mg tetraaminophenylenediamine were dissolved in 20 mL of a mixed solvent of o-dichlorobenzene and n-butanol at a volume ratio of 1:1, and ultrasonic treatment was used to ensure uniform dispersion;

[0029] Add 6.587 mg of trialdehyde triphenylamine and 100 μL of acetic acid to the solution and transfer to a 100 mL reactor;

[0030] React in a constant temperature environment of 60°C for 48 hours;

[0031] After the reaction was completed, the MXene / COF composite was separated and washed with anhydrous ethanol;

[0032] The solvent and water were removed by freeze drying to obtain MXene / COF composite material powder.

[0033] Preferably, the power density calculation formula of the electrode material of the supercapacitor module is:

[0034]

[0035] Where E is the energy density and Δt is the discharge time.

[0036] Preferably, the control circuit comprises:

[0037] A charging module, used to charge the supercapacitor module in advance on the ground;

[0038] A discharge control module is used to start the supercapacitor module and discharge the hot knife assembly after the satellite enters orbit;

[0039] The temperature monitoring module is used to monitor the temperature of the hot knife in real time to ensure that it works within a safe range.

[0040] Preferably, the step of configuring the electrolyte further included in step three specifically includes:

[0041] 9.25 m bis(trifluoromethanesulfonyl)imide lithium salt and 21 m bis(trifluoromethanesulfonyl)imide lithium salt were dissolved in dimethyl carbonate and deionized water respectively;

[0042] The mixture is mixed in a mass ratio of 1:1 to prepare an electrolyte.

[0043] Preferably, the preparation steps of the MXene, COF, MXene / COF (MCF) electrode specifically include:

[0044] MXene, COF, and MXene / COF (MCF) powders were mixed with N-methylpyrrolidone to form a slurry;

[0045] Apply the slurry onto the current collector, ensuring even distribution;

[0046] The electrode was dried under vacuum at 80° C. for 12 hours to obtain a dry electrode sheet.

[0047] Preferably, the step three further includes the steps of preparing the activated carbon electrode, which specifically include:

[0048] The activated carbon, the conductive agent which is conductive carbon black, and the binder which is polytetrafluoroethylene dispersion are mixed in a mass ratio of 8:1:1, and ground until uniform;

[0049] Roll the mixed slurry into sheets to ensure uniform thickness;

[0050] Dry at room temperature for 12 hours;

[0051] Use a cutting machine to cut into 12mm diameter discs for later use.

[0052] The present invention provides a hot knife power supply technology for deploying satellite solar panels based on supercapacitors. It has the following beneficial effects:

[0053] 1. In order to achieve the effective combination of COF particles and MXene, this study adopts a hydrothermal-assisted synthesis method. This method uses chemical reactions under hydrothermal conditions to enable COF particles to grow in situ on the surface of MXene, thereby forming a new type of MXene / COF (MCF) composite material. This synthesis strategy not only ensures the close combination between COF particles and MXene, but also helps to maintain the original two-dimensional structure and high conductivity of MXene. By precisely controlling the conditions of the hydrothermal reaction, such as temperature, time, precursor concentration, etc., the growth process of COF on the MXene surface can be optimized, thereby obtaining an MCF composite material with ideal structure and performance.

[0054] 2. By combining the high conductivity of MXene with the porous structure of COF, the MCF composite material not only increases its specific surface area, but also improves the efficiency of ion migration. The conductivity of MXene provides a pathway for the rapid transmission of electrons, while the porous structure of COF provides abundant channels for the diffusion and migration of ions. This synergistic effect enables MCF composite materials to exhibit excellent performance in electrochemical applications, such as in supercapacitors, batteries, and electrocatalysis. In addition, increasing the specific surface area also helps to increase the number of active sites in the material, thereby further improving its electrochemical performance.

[0055] 3. The present invention has made innovative changes to the deployment and recovery methods of satellite solar panels, which significantly improves the efficiency of electric energy use. Through optimized design, the new deployment and recovery mechanism not only simplifies the structure and reduces potential failure points, but also improves the reliability and efficiency of operation. This improvement can ensure that solar panels operate more stably and persistently in the space environment, thereby improving the energy collection efficiency of satellites, extending the life of satellites, and reducing maintenance costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 is a flow chart of the preparation process of COF of the present invention;

[0057] Figure 2 TiVAlCMAX and TiVCT of the present invention x Schematic diagram of XRD pattern of MXene;

[0058] Figure 3 The TiVCT of the present invention x Schematic diagram of XRD patterns of MXene, COF, and MCF;

[0059] Figure 4 The infrared spectra of MXene, COF and MCF of the present invention are shown;

[0060] Figure 5 It is a schematic diagram of the SEM image of the material of the present invention;

[0061] Figure 6 Schematic diagram of contact angle of the present invention;

[0062] Figure 7 A schematic diagram of capacitance values ​​at different scanning rates obtained by calculating the integral area of ​​the CV curve of the present invention;

[0063] Figure 8 It is a schematic diagram of the CV curve of the present invention;

[0064] Fig. 9 It is a schematic diagram of the GCD curve of the present invention;

[0065] Fig.10 It is a schematic diagram of the Nyquist diagram of the present invention. DETAILED DESCRIPTION

[0066] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0067] Embodiment 1:

[0068] Please see attached Figure 1 - Attachment Fig.10 The embodiment of the present invention provides a hot knife power supply technology for deploying satellite solar panels based on supercapacitors, including:

[0069] Supercapacitor modules for storing electrical energy;

[0070] The hot knife assembly is made of high-resistance material and generates heat instantly when powered on, and is used to cut the fixtures of the solar panels;

[0071] A control circuit, including a charging module, a discharging control module and a temperature monitoring module;

[0072] The supercapacitor module includes MXene and COF composite electrodes, which are prepared by the following steps:

[0073] Step 1: Etch TiVAlC powder to obtain TiVCT x MXene;

[0074] Step 2: Mix tetraaminophenylenediamine and trialdehyde triphenylamine, dissolve them and heat them to react to obtain COF;

[0075] Step 3: React MXene with tetraaminophenylenediamine and trialdehyde triphenylamine solution under hydrothermal conditions to form a MXene / COF composite material.

[0076] Step 1: Material Selection

[0077] In this embodiment, TiVCT is selected x MXene and COF (covalent organic framework) are used as composite materials. TiVCTxMXene has high conductivity and COF has high specific surface area. The combination of the two can construct high-performance electrode materials. Through this material combination, the electrochemical performance of supercapacitors can be effectively improved, providing higher energy density and power density.

[0078] Step 2: Composite electrode preparation.

[0079] In this embodiment, COF is grown in situ between MXene nanosheets by hydrothermal-assisted synthesis to ensure effective combination of COF particles and MXene. The specific steps are as follows:

[0080] Preparation of mixed solution: 2 mg of MXene and 7 mg of Tp (tetraaminophenylenediamine) were dissolved in 20 mL of a mixed solvent (o-dichlorobenzene and n-butanol, volume ratio 1:1).

[0081] Ultrasonic treatment: Ultrasonic treatment was used to ensure that MXene and Tp were evenly dispersed in the solvent.

[0082] Preparation of reaction solution: 6.587 mg of TFA (triadialdehyde triphenylamine) and 100 μL of acetic acid were added to the solution.

[0083] Hydrothermal reaction: The reaction solution was transferred to a 100 mL reactor and reacted at a constant temperature of 60 °C for 48 hours.

[0084] Cleaning and drying: After the reaction is completed, the obtained MXene / COF composite material is separated and cleaned with anhydrous ethanol, and then freeze-dried to obtain MXene / COF composite material powder.

[0085] Through the above steps, the obtained MXene / COF composite material can significantly improve the conductivity and ion conduction efficiency of the electrode, providing a guarantee for the high performance of the supercapacitor.

[0086] TiVCT x Preparation of MXene

[0087] In this embodiment, TiVCT x The preparation steps of MXene specifically include:

[0088] Solution preparation: Add 1.0 g of lithium fluoride to 20.0 mL of 9 M hydrochloric acid aqueous solution and stir for 20 minutes.

[0089] Add TiVAlC: slowly add 1.0 g of TiVAlC powder, transfer to an oil bath, and react at 45°C for 48 hours.

[0090] Centrifugation and washing: After the reaction is completed, centrifuge at 3500rpm for 5 minutes, remove the supernatant, and repeat washing until the pH is neutral to obtain TiVCT. x MXene aqueous solution.

[0091] Freeze drying: TiVCT x Freeze drying of MXene aqueous solution to obtain TiVCT x MXene powder.

[0092] This step ensures the purity and performance of the MXene material through fine chemical treatment and physical separation, providing high-quality basic materials for subsequent electrode preparation.

[0093] Preparation of COF

[0094] In this embodiment, the preparation steps of COF specifically include:

[0095] Solution preparation: 0.015 mM tetraaminophenylenediamine (Tp) and 0.02 mM trialdehyde triphenylamine (TFA) were dissolved in 10 mL of a mixed solvent of o-dichlorobenzene and n-butanol in a volume ratio of 1:1.

[0096] Heating reaction: heating the reaction at 120°C for 48 hours.

[0097] Separation and washing: After the reaction is completed, the COF solid is separated by suction filtration and washed with anhydrous ethanol.

[0098] Freeze drying: Freeze drying is used to remove the solvent and water in COF to obtain COF powder.

[0099] Through the above steps, the preparation process of COF can ensure that it has a high specific surface area and good electrochemical activity, providing high-quality materials for the preparation of composite electrodes.

[0100] Electrolyte configuration

[0101] In this embodiment, the steps of configuring the electrolyte specifically include:

[0102] Dissolution process: 9.25 mL LiTFSI and 21 mL LiTFSI were dissolved in DMC (dimethyl carbonate) and deionized water, respectively.

[0103] Mixing process: The two solvents are mixed in a mass ratio of 1:1 to prepare an electrolyte.

[0104] The electrolyte configuration process ensures high conductivity and stability of the electrolyte, which is suitable for efficient charging and discharging of supercapacitors.

[0105] Preparation of electrode sheets

[0106] In this embodiment, the steps of preparing the electrode sheet specifically include:

[0107] Preparation of MXene, COF, and MXene / COF (MCF) electrodes

[0108] Slurry preparation: MXene, COF, and MXene / COF (MCF) powders were mixed with NMP (N-methylpyrrolidone) to form slurry.

[0109] Coating process: The slurry is coated on the current collector (such as copper foil or aluminum foil) to ensure uniform distribution.

[0110] Drying process: vacuum drying at 80°C for 12 hours to obtain a dry electrode sheet.

[0111] Preparation of activated carbon electrodes

[0112] Material mixing: Mix activated carbon, conductive agent SuperP, and binder PTFE dispersion in a mass ratio of 8:1:1 and grind until uniform.

[0113] Rolling into sheets: Roll the mixed slurry into sheets to ensure uniform thickness.

[0114] Cutting process: Dry at room temperature for 12 hours, and use a cutting machine to cut into round pieces with a diameter of 12 mm for later use.

[0115] Electrochemical testing

[0116] In this embodiment, the electrochemical performance of the supercapacitor is tested by the following steps:

[0117] Three-electrode system test

[0118] Electrode configuration: MXene, COF, MXene / COF (MCF) electrodes were used as working electrodes, Ag / AgCl electrode was used as reference electrode, and activated carbon was used as counter electrode to form a three-electrode system.

[0119] Electrochemical tests: Cyclic voltammetry (CV) and constant current charge-discharge (GCD) tests were performed in a three-electrode system.

[0120] The specific capacitance of the electrode material is calculated as:

[0121]

[0122] Asymmetric supercapacitor assembly and testing

[0123] Supercapacitor assembly: An asymmetric supercapacitor was assembled using MCF as the negative electrode and activated carbon as the positive electrode.

[0124] Electrochemical performance test: CV test, GCD test and electrochemical impedance spectroscopy (EIS) test were performed.

[0125] The energy density of supercapacitors is calculated as:

[0126]

[0127] Where C is the capacitance and ΔV is the operating voltage.

[0128] The power density of supercapacitors is calculated as:

[0129]

[0130] Where E is the energy density and ΔV is the discharge time.

[0131] Electrochemical impedance spectroscopy (EIS) testing analyzes the impedance characteristics of capacitors and determines ion transport and charge transfer impedances.

[0132] Hot knife power system components

[0133] In this embodiment, the hot knife power supply system specifically comprises:

[0134] Supercapacitor module: Provides high power pulses for instantaneous heating of the hot knife.

[0135] Hot knife assembly: Made of high-resistance material, it generates heat instantly when powered on and is used to cut the fixings of solar panels.

[0136] Control circuit: includes charging module, discharge control module and temperature monitoring module to ensure the stability and safety of the system.

[0137] The design and combination of these components ensures efficient operation and reliability of the Hot Knife power system.

[0138] Working Principle of Hot Knife Power Supply

[0139] In this embodiment, the working principle of the hot knife power supply is as follows:

[0140] Charging: The supercapacitor module is charged in advance on the ground to store electrical energy.

[0141] Discharge: After the satellite enters orbit, the control circuit starts the supercapacitor module to discharge the hot knife assembly.

[0142] Heating: The hot knife assembly heats up instantly, cutting the solar panel's fixtures and releasing the solar panel to unfold.

[0143] Monitoring: The temperature monitoring module during the discharge process monitors the temperature of the hot knife in real time to ensure that it operates within a safe range.

[0144] The above working principle ensures the reliable deployment of the satellite solar panels and the efficient operation of the system.

[0145] System Integration and Optimization

[0146] In this embodiment, the system integration and optimization steps specifically include:

[0147] Optimize supercapacitor design: Increase the specific surface area and ion migration efficiency of the electrode material by adjusting the composite ratio of MXene and COF.

[0148] Introducing conductive materials: Introducing carbon nanotubes into MXene / COF composites can further improve the conductivity and electron transfer rate of the material.

[0149] Improved hot knife design: Use high-efficiency thermal conductive materials to increase the working efficiency and life of the hot knife.

[0150] In a preferred embodiment, the improved supercapacitor module design

[0151] Based on the above-mentioned implementation manner, this preferred embodiment further optimizes the design of the supercapacitor module, especially the optimization of electrode materials and the selection of electrolyte.

[0152] Improved supercapacitor module design

[0153] Optimization of electrode materials

[0154] In this embodiment, the composite ratio of MXene and COF is further optimized, and carbon nanotubes are introduced as additional conductive materials. The specific steps are as follows:

[0155] Composite material preparation:

[0156] Preparation of MXene: TiVCT was prepared using the aforementioned method x MXene.

[0157] Preparation of COF: COF was prepared using the method described above.

[0158] Preparation of composite materials: Add an appropriate amount of carbon nanotubes to the solution of MXene and COF, disperse them evenly by ultrasonication, and react the solution in a constant temperature environment of 60°C for 48 hours to obtain a MXene / COF / CNT composite material.

[0159] Cleaning and drying: After the reaction is completed, the obtained MXene / COF / CNT composite material is separated and cleaned with anhydrous ethanol, and then freeze-dried to obtain a composite material powder.

[0160] Preparation of electrode sheets:

[0161] Slurry preparation: Mix MXene / COF / CNT powder and NMP evenly to form slurry.

[0162] Coating and drying: Coat the slurry on the current collector (such as copper foil or aluminum foil) to ensure uniform distribution. Dry it in vacuum at 80°C for 12 hours to obtain a dry electrode sheet.

[0163] Selection of electrolyte

[0164] In this embodiment, the selection of the electrolyte is further optimized, as follows:

[0165] Mixed electrolyte: 9.25 mL LiTFSI and 21 mL LiTFSI were dissolved in a mixed solvent of DMC (dimethyl carbonate), PC (propylene carbonate) and EC (ethylene carbonate) (volume ratio of 2:2:1) to ensure that the electrolyte has higher conductivity and stability.

[0166] Preparation process: Mix in a mass ratio of 1:1:1 to prepare the electrolyte.

[0167] Through the above optimization, the supercapacitor module of this preferred embodiment has significantly improved energy density and power density, and has higher cycle stability and longer service life.

[0168] These optimization measures ensure the high performance and reliability of the system to adapt to the harsh conditions of the space environment.

[0169] In a preferred embodiment, the improved hot knife assembly design

[0170] Optimization of hot knife materials

[0171] In this embodiment, the material selection of the hot knife is further optimized, and a composite material with high thermal conductivity and high resistivity is used. The specific steps are as follows:

[0172] Hot knife material preparation:

[0173] Material selection: Silicon carbide (SiC) and aluminum nitride (AlN) are selected as the main materials of the hot knife to ensure that they have high thermal conductivity and high resistivity.

[0174] Material synthesis: Silicon carbide and aluminum nitride are mixed by high-temperature sintering to produce a high-performance composite hot knife.

[0175] Forming: Processing the synthesized composite material into the shape and size required by the hot knife to ensure that it can effectively heat and cut the solar panel fixture when working.

[0176] Improved control circuit design

[0177] Control circuit optimization

[0178] In this embodiment, the design of the control circuit is further optimized, as follows:

[0179] Charging module: Added current control and voltage monitoring functions to ensure the safety and stability of the supercapacitor module when charging on the ground.

[0180] Discharge control module: It uses an intelligent control chip to achieve precise control of the hot knife assembly to ensure stability and efficiency during the discharge process.

[0181] Temperature monitoring module: Added multi-point temperature monitoring function to monitor the temperature changes of the hot knife in real time to ensure that it works within a safe range.

[0182] Experimental evidence:

[0183] Material characterization

[0184] X-ray diffraction (XRD) analysis

[0185] Through X-ray diffraction (XRD) analysis, TiVAlCMAX, TiVCT x MXene, COF, and MXene / COF (MCF) were tested, and the results are shown below:

[0186] Figure 1 It shows that after selective etching of TiVAlC, TiVCT at a diffraction angle of 7.36° x MXene has a distinct (002) diffraction peak, proving that TiVCT x Successful preparation of MXene.

[0187] Figure 2 It shows that after MXene is assembled with COF, the crystal plane diffraction peak of MXene moves from 7.36° to 7.29°, indicating that the addition of COF expands the interlayer spacing of the electrode material.

[0188] Fourier transform infrared spectroscopy (FTIR) analysis

[0189] In order to understand the distribution of functional groups on the sample surface, infrared spectroscopy tests were performed on MXene, COF, and MCF samples. The results are shown in the figure:

[0190] MXene at 3441, 1596 and 1366 cm -1 There are obvious characteristic peaks at , which correspond to the vibration of the hydroxyl functional group and the symmetric and asymmetric stretching vibration of CO.

[0191] COF samples at 1500, 1593, 1264 cm -1 There are characteristic peaks at , which are related to the vibration of C=C and the stretching vibration of two COs.

[0192] Scanning electron microscopy (SEM) analysis

[0193] The microscopic morphology of the material was observed by scanning electron microscopy (SEM) test, and the results are shown as follows:

[0194] Figure 5 (a) shows that the TiVAlCMAX phase powder has a stepped morphology.

[0195] Figure 5(b) shows that after etching and peeling off the MAX phase, flake TiVCTxMXene was successfully prepared.

[0196] Figure 5 (c) shows that the COF powder is spherical.

[0197] Figure 5 (d) shows that the cross-section of the MXene electrode is stacked layer by layer.

[0198] Figure 5 Middle (e) shows that the MCF electrode plane is wrinkled, which expands the contact area and is conducive to the infiltration of the electrolyte.

[0199] Figure 5 (f) shows that in the cross-section of the MCF electrode, COF is attached to the electrode layer in a spherical shape.

[0200] Contact angle test

[0201] In order to explore the wetting ability of the electrolyte on different electrode materials, the electrolyte was dripped on the MXene, COF, and MCF electrode materials, and their contact angles were measured. The results are shown below:

[0202] Figure 6 (a) shows that the contact angle of the electrolyte droplet on the MXene material is 71.653°.

[0203] Figure 6 (b) shows that the contact angle of the electrolyte droplet on the COF material is 41.964°.

[0204] Figure 6 (c) shows that the contact angle of the electrolyte droplet on the MCF material is 38.754°.

[0205] It can be seen that MCF materials have better wettability in electrolytes, are more conducive to contact with ions in the electrolyte, increase charge transfer efficiency, and promote the improvement of electrochemical performance.

[0206] Electrochemical performance test

[0207] Three-electrode test:

[0208] The electrochemical performance of MXene, COF, and MCF electrodes were tested in a three-electrode system. The CV curve results are shown in Figure 7 As shown in (a), (b) and (c), it shows good reversibility.

[0209] Figure 7(d) shows that at 2 mV / s, the mass specific capacitance of the MXene electrode is 27.0 F / g, the COF electrode is 26.1 F / g, and the MCF electrode is 42.3 F / g, indicating that the specific capacitance of the composite material is significantly improved.

[0210] MCF / / AC supercapacitor electrochemical performance test:

[0211] The MCF / / AC supercapacitor was assembled and the electrochemical performance was tested. The results are shown below.

[0212] Figure 8 It shows that the CV curves of the MCF / / AC supercapacitor at 5mV / s and 8mV / s have good electrochemical response with a voltage window of 2.0V.

[0213] Fig. 9 The GCD curve is quasi-triangular in shape and has a good Coulomb efficiency (98%).

[0214] Fig.10 It shows that the Nyquist plot has a larger slope in the low-frequency region, indicating excellent ion transmission capability.

[0215] Comparative Example 1:

[0216] Pulse modulation hot knife power supply system:

[0217] Using pulse width modulation (PWM) control technology, the discharge speed and current of the supercapacitor can be finely adjusted to accurately control the temperature and heating time of the hot knife. The system can set different PWM modes through software programming to adapt to different operating scenarios, such as unfolding tasks under different ambient temperatures. PWM technology also helps reduce energy waste and improve overall energy efficiency.

[0218] Comparative Example 2:

[0219] Reusable Hot Knife Cycle Power System:

[0220] The system is designed to be able to perform multiple deployment operations at different mission stages, and the supercapacitors allow for rapid recharging after partial discharge, without having to wait for full discharge. This design increases the flexibility and application range of the system, and is suitable for the needs of multiple deployments of solar panels in long-term missions. The capacitor selection and management system will ensure the long-term stability and reliability of the capacitors.

[0221] Experimental Project Embodiment 1 Comparative Example 1 Comparative Example 2 Energy density 20 18 19 Power density 10000 8000 9000 Cycle life 100000 80000 90000 Heating efficiency 95 90 92

[0222] Table 1

[0223] By comparing the experimental data, Example 1 shows significant advantages in energy density, power density, cycle life and heating efficiency. Therefore, the preferred embodiment of the present invention significantly improves the performance and reliability of the hot knife power supply technology for deploying satellite solar panels based on supercapacitors, is suitable for more stringent space environments, and meets practical application needs.

[0224] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A hot knife power supply technology for deploying satellite solar panels based on supercapacitors, characterized in that: include: Supercapacitor modules for storing electrical energy; The hot knife assembly is made of high-resistance material and generates heat instantly when powered on, and is used to cut the fixtures of the solar panels; A control circuit, including a charging module, a discharging control module and a temperature monitoring module; The supercapacitor module includes a MXene and COF composite electrode, and the composite electrode is prepared by the following steps: Step 1: Etch TiVAlC powder to obtain TiVCT x MXene; Step 2: Mix tetraaminophenylenediamine and trialdehyde triphenylamine, dissolve them and heat them to react to obtain COF; Step 3: React MXene with tetraaminophenylenediamine and trialdehyde triphenylamine solution under hydrothermal conditions to form a MXene / COF composite material.

2. The hot knife power supply technology for deploying satellite solar panels based on supercapacitors according to claim 1 is characterized in that: In the step 3, the specific capacitance calculation formula of the electrode material is: Where I is the discharge current, Δt is the discharge time, m is the mass of the electrode material, and ΔV is the voltage change.

3. The hot knife power supply technology for deploying satellite solar panels based on supercapacitors according to claim 1 is characterized in that: The TiVCT x The preparation steps of MXene specifically include: Add 1.0 g of lithium fluoride to 20.0 mL of 9 M hydrochloric acid solution and stir for 20 minutes; Slowly add 1.0 g TiVAlC powder, transfer to an oil bath, and react at 45 °C for 48 hours; After the reaction, the mixture was centrifuged at 3500 rpm for 5 minutes using an ultra-high speed centrifuge, the supernatant was removed, and the mixture was washed repeatedly until the pH was neutral to obtain TiVCT. x MXene aqueous solution; The obtained TiVCT x Freeze drying of MXene aqueous solution to obtain TiVCT x MXene powder.

4. The hot knife power supply technology for deploying satellite solar panels based on supercapacitors according to claim 1 is characterized in that: The preparation steps of the COF specifically include: Dissolve 0.015 mM tetraaminophenylenediamine and 0.02 mM trialdehyde triphenylamine in 10 mL of a mixed solvent of o-dichlorobenzene and n-butanol in a volume ratio of 1:1; The reaction was heated at 120°C for 48 hours; After the reaction was completed, the COF solid was separated by suction filtration and washed with anhydrous ethanol; The COF powder was obtained by freeze drying to remove the solvent and water in the COF.

5. The hot knife power supply technology for deploying satellite solar panels based on supercapacitors according to claim 1 is characterized in that: The preparation steps of the MXene / COF composite material specifically include: 2 mg MXene and 7 mg tetraaminophenylenediamine were dissolved in 20 mL of a mixed solvent of o-dichlorobenzene and n-butanol at a volume ratio of 1:1, and ultrasonic treatment was used to ensure uniform dispersion; Add 6.587 mg of trialdehyde triphenylamine and 100 μL of acetic acid to the solution and transfer to a 100 mL reactor; React in a constant temperature environment of 60°C for 48 hours; After the reaction was completed, the MXene / COF composite was separated and washed with anhydrous ethanol; The solvent and water were removed by freeze drying to obtain MXene / COF composite material powder.

6. The hot knife power supply technology for deploying satellite solar panels based on supercapacitors according to claim 1 is characterized in that: The power density calculation formula of the electrode material of the supercapacitor module is: Where E is the energy density and Δt is the discharge time.

7. The hot knife power supply technology for deploying satellite solar panels based on supercapacitors according to claim 1 is characterized in that: The control circuit comprises: A charging module, used to charge the supercapacitor module in advance on the ground; A discharge control module is used to start the supercapacitor module and discharge the hot knife assembly after the satellite enters orbit; The temperature monitoring module is used to monitor the temperature of the hot knife in real time to ensure that it works within a safe range.

8. The hot knife power supply technology for deploying satellite solar panels based on supercapacitors according to claim 1 is characterized in that: The step of configuring the electrolyte in step 3 specifically includes: 9.25 m bis(trifluoromethanesulfonyl)imide lithium salt and 21 m bis(trifluoromethanesulfonyl)imide lithium salt were dissolved in dimethyl carbonate and deionized water respectively; The mixture is mixed in a mass ratio of 1:1 to prepare an electrolyte.

9. The hot knife power supply technology for deploying satellite solar panels based on supercapacitors according to claim 1, characterized in that: The preparation steps of the MXene, COF, and MXene / COF (MCF) pole pieces specifically include: MXene, COF, and MXene / COF (MCF) powders were mixed with N-methylpyrrolidone to form a slurry; Apply the slurry onto the current collector, ensuring even distribution; The electrode was dried under vacuum at 80° C. for 12 hours to obtain a dry electrode sheet.

10. The hot knife power supply technology for deploying satellite solar panels based on supercapacitors according to claim 1, characterized in that: The step 3 also includes the steps of preparing the activated carbon electrode, which specifically include: The activated carbon, the conductive agent which is conductive carbon black, and the binder which is polytetrafluoroethylene dispersion are mixed in a mass ratio of 8:1:1, and ground until uniform; Roll the mixed slurry into sheets to ensure uniform thickness; Dry at room temperature for 12 hours; Use a cutting machine to cut into 12mm diameter discs for later use.

Citation Information

Patent Citations

  • Satellite-rocket separation heat knife unlocking system and method

    CN107294166A

  • Covalent organic framework / MXene composite film material as well as preparation method and application thereof

    CN116759520A

  • COF-MXene composite material as well as preparation method and application thereof

    CN117567709A

  • Preparation method and application of 3D printing polydiaminonaphthalene / graphene composite electrode

    CN118016451A

  • Conductive two-dimensional (2D) covalent organic frameworks (COFS) and method of making an electrode material

    WO2021245559A1